THE COMBINATION THERAPY MODEL OF Andrographis paniculata EXTRACT AND CHLOROQUINE ON Plasmodium berghei INFECTED MICE - Hafid, Achmad Fuad (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The aim was to determine the antimalarial drug effectiveness of the combination therapy model of 80% ethanolic extract of sambiloto (EES) and chloroquine on Plasmodium berghei infected mice. Methods: Five groups of P. berghei infected mice were used in this study, divided by three combinations therapy models of EES and chloroquine groups (Model A, B, C), one monotherapy of EES group (Model D) and one untreated group (Model E) as a control. EES and chloroquine were used at a dose of 100 mg/kg mice body weight and 0.15 mg/kg mice body weight, respectively. Only for Model C, chloroquine was used at a dose of 10 mg/kg mice body weight. Three combinations therapy models consisted of Model A: Infected mice treated by EES and chloroquine for 4 days; Model B: treated by EES for 4 days and chloroquine for 1 day at 1st day; Model C: treated by EES for 4 days and chloroquine for 1 day at 4th day. Meanwhile, Model D and E were treated by EES and vehicle each for 4 days, respectively. Blood smear of all mice was prepared with Giemsa stain. Antimalarial activity was determined by the difference between the mean value of parasitemia of control (Model E, taken as 100%) and those of the experimental group (Model A, B, C and D). Results: Three combination therapy models (Model A, B, C) and one monotherapy (Model D) were showed antimalarial activities against parasite with inhibition of parasite growth by 85.61%, 69.31%, 73.64% and 65.14%, respectively. Conclusion: Model A was showed as the most effective combination therapy model on mice infected by malaria. The results indicated that combination therapy model of EES and chloroquine were able to increase the antimalarial effectiveness by 85.61% inhibition of parasite growth and having smaller risk of resistance by using low dose of chloroquine (0.15 mg/kg mice body weight). Keywords: Antimalarial combination therapy, Andrographis paniculata, Chloroquine.